Quantitative EEG analysis disease during resting and memory task in carriers and non-carriers of PS-1 E280A mutation of familial Alzheimer´s (2014)
ABSTRACT: Background: Alzheimer’s disease is the most leading cause of dementia in the world; the mutation PS-1 E280A alters the gene of the Presenilin-1 and causes an early onset familial Alzheimer’s disease. This mutation has been found in large kindred of Antioquia, Colombia. The objective of this study was to find differences revealed by electroencephalogram between healthy subjects and asymptomatic carriers that can be used as clinical markers of the disease in this population. Methods: EEG was recorded in 15 asymptomatic E280A carriers and 15 healthy non carriers during resting and a memory task using 64 channels amplifier. Two conditions in the memory task were analyzed: encoding and retrieval, the process of recording and evocating information, respectively. Power spectrum was calculated in delta (0.5–4.0 Hz), theta (4.0–8. 0 Hz), alpha-1 (8.0–10.0 Hz), alpha-2 (10.0–13.0 Hz), beta (13.0–25.0 Hz) and gamma (25.0–50 Hz) frequency bands for four regions of interest. Changes were evaluated in different conditions by ANOVA analysis. Results: In resting condition a significant decrease was found in theta (p=0. 0001) and an increase in alpha-2 frequencies (p=0.037) in carriers compare with controls. During encoding of the memory task theta was significantly lower in carriers compared with controls (p=0. 008) and comparing resting versus retrieval process for each group, there was more theta synchronization in carriers. Conclusion: Early changes in theta frequencies were observed in the EEG recordings, it could be use as clinical markers in this population. Also it seems carriers activate additional cortical regions in order to conserve successful cognitive functions before clinical impairment.